Clinical outcomes and survival comparison between NexGen all-poly and its metal-backed equivalent in total knee arthroplasty - Apostolopoulos, Vasileios; Nachtnebl, Luboš; Mahdal, Michal; Pazourek, Lukáš; Boháč, Petr; Janíček, Pavel; Tomáš, Tomáš (International orthopaedics, 2023)
PURPOSE: This study aims to compare total knee replacement (TKA) with NexGen All-Poly (APT) and NexGen Metal-Backed (MBT) in terms of implant survivorship, reasons leading to implant failure and functional results of defined age categories. METHODS: A single-centre, retrospective evaluation of 812 patients who underwent knee replacement with NexGen CR between 2005 and 2021, comparing a modern congruent APT component to a modular MBT equivalent component using a similar surgical technique at a notable mean follow-up duration. Implant survival, functional outcomes using the Knee Society Score and range of motion were evaluated and compared in different age categories. RESULTS: Of the 812 NexGen CR TKAs performed at our institution, 410 (50.4%) used APT components and 402 (49.6%) MBT components. The survival rate of NexGen APT was 97.1% and that of NexGen MBT was 93.2% (p = 0.36). Removal of the implant occurred overall in 15 cases, for MBT in ten cases, and for APT in four cases. The FS was proved to be significantly higher when APT components were implanted in younger patients than for MBT (p = 0.005). A similar range of motion between the components was recorded (p = 0.1926). CONCLUSION: Under defined conditions, we measured the clinical results of implants from a single manufacturer implanted in a single department using a similar surgical technique. Considering the limitations, we suggest that all-polyethylene tibial components are equal or even superior to metal-backed ones across the examined age categories.
Keywords: All-polyethylene knee replacement; Knee Society Score; Knee arthroplasty; Prosthesis Design; NexGen; protézy - design; Metals; Polyethylene; lidé; Knee Prosthesis; Implant survival; kovy; retrospektivní studie; protézy kolene; polyethylen; Arthroplasty, Replacement, Knee; Retrospective Studies; totální endoprotéza kolene; Humans